Reducing Pre-Analytical Specimen Rejection Through Collaborative Interventions Between Nursing And Laboratory Professionals: A Systematic Review And Meta-Synthesis Of Prior Literature (The Review of Diabetic Studies, 2024)
Background: The pre-analytical phase of the Total Testing Process (TTP) is recognized as the most vulnerable period in diagnostic testing, accounting for up to 70% of all clinical laboratory errors. In decentralized phlebotomy settings, nurses and frontline clinical staff bear primary responsibility for specimen collection, yet historical silos between nursing wards and clinical laboratories frequently precipitate miscommunication, standardized protocol deviations, and elevated specimen rejection rates.Objectives: This systematic review and meta-synthesis aim to systematically identify, appraise, and synthesize prior literature evaluating the efficacy of interdisciplinary, collaborative interventions between nursing and laboratory professionals in reducing pre-analytical specimen rejection.Data Sources: A comprehensive, systematic literature search was conducted across major electronic databases, including PubMed/MEDLINE, CINAHL, Scopus, and the Cochrane Library, strictly restricting inclusion to peer-reviewed evidence published prior to 2024.Review Methods: The review protocol adheres strictly to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Quality appraisal of the included literature was conducted utilizing the Mixed Methods Appraisal Tool (MMAT) and the Cochrane Risk of Bias tools. Data synthesis utilized a thematic meta-synthesis approach to categorize intervention typologies and extract comparative quality indicators.Results: A rigorous synthesis of the prior literature identified distinct operational themes among successful collaborative interventions: joint interprofessional education (IPE) modules, shared governance quality committees, implementation of synchronized technological solutions (e.g., barcode specimen tracking), and standard operating procedure (SOP) harmonizations. Prior evidence strongly indicates that moving from departmental silos to integrated, interdisciplinary workflows yield statistically significant reductions in pre-analytical errors, specifically hemolysis and mislabeling.Conclusion: Collaborative, systems-level interventions bridging the nursing-laboratory divide serve as a critical healthcare quality management strategy. By fostering shared accountability and continuous interdisciplinary communication, healthcare institutions can sustainably reduce specimen rejection, thereby mitigating unnecessary financial burdens, preventing diagnostic delays, and fundamentally enhancing patient safety.